Peran Orang Tua dalam Pendampingan Anak Usia Dini Bermain Gadget - Ratih Agustin Wulandari; Erlina Purwaningsih; Darussalam Darussalam; Oktaviani Oktaviani; Wandira Wandira (Yayasan Literasi Sains Indonesia, 2023)
The form of parental assistance provided is only in the form of advice, but there are also children who do not receive attention or assistance in their daily lives because parents are busy working. This study aims to analyze the role of parents in accompanying early childhood playing gadgets. This type of research is qualitative research. The study was conducted by parents and children aged 2 years and 7 months with the subject being 1 toddler and 1 toddler's parents in Jorong Sungai Atang, Kenagarian Batu Rijal, Padang Lawas District, Dharmasraya Regency. Methods of data collection using interviews, observation, and documentation. Data analysis using qualitative analysis. The results showed that the toddler's parents were busy working, namely sewing. The obstacle is that parents do not understand the dangers and effects of using gadgets for early childhood. The solution to overcome the obstacles faced by parents in assisting young children to play gadgets is to accompany children in every activity, invite them to talk, teach children to socialize with neighbors, invite children to play outside the home. Therefore, parents can set time limits for using gadgets, be selective in choosing applications for children, accompany children when using gadgets, train children to be responsible for using gadgets and parents try to supervise children in social interaction properly.